X頻帶雙飄移高低高矽衝渡二極體之準靜態設計規範 - 張懋中; 陳茂傑; Mau-Chung Chang; Mao-Chieh Chen (My University, 1976)
A modified quasi-static model is developed to optimize the power efficiency of double-drift X-band Lo-Hi-Lo IMPATT diodes. We take the ionization rates and scattering-limited velocities for electrons and holes to be not equal at an operation temperature of 150 ℃, and let the carriers' ionization coefficient be in the form α=A*exp(-B/E),where E is the electric field.We maintain the carriers' velocities at saturation and solve for a steady state solution. All these assumptions not only save computer time, but also give us essential physical features.Current tuning effect is concluded as the most important factor in designing the device structure.Large signal values of negative conductance, susceptance,r.f. power generation efficiency are calculated as a function of the oscillation voltage amplitude for a specified bias current density. All of these informations would provide a useful guidance for both device and circuit designers.
Quasi-Static Design Considerations of X-Band Double Drift Lo-Hi-Lo Silicon IMPATT Diodes